PEMANFAATAN MEDIA DIGITAL DALAM PELAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH DASAR : Kajian teori - Sandra Lidia; Leni Murni Hayati (Jurnal Pendidikan Widyaswara Indonesia, 2025)
The development of digital technology has had a significant impact on the education sector, including on guidance and counseling services at the elementary school level. The purpose oh this article is to analyze the functions and benefits of using digital media to support the effectiveness of guidance and counseling services in elementary schools. The writing method is carried out by a literature study that examines various sources, journals, and relevant trusted references. The findings of the study indicate that digital media such as educational videos, communication platforms, and interactive applications, facilitate the delivery of materials, and expand access to guidance and counseling services. However, the success of their use is highly dependent on teacher readiness, available technological facilities, and support from the school environment. Therefore, the use of digital media needs to be balanced with teacher training and the provision of adequate facilities. This article is expected to be a reference in the development of guidance and counseling services that are responsive to technological advances.